Quando Dio parla (medio-)francese: Prologue e Fin nei Mystères de la Procession de Lille (XV secolo) (Altre Modernità, 2011)
Within the Mystères de la Procession de Lille, Prologue and Fin take on a specific extratextual  function: they introduce, comment and make topical the biblical episodes they stage. Appearing  regularly and according to a recurrent and repeated pattern, they prove essential as a tool to ensure the authenticity of the text and the effectiveness of the moral they posit.
Keywords: teatro francese; XV secolo; Mystères de la Procession de Lille